Optimization of ozonation combined with integrated fixed-film activated sludge (IFAS) in the treatment of oil sands process-affected water (OSPW). (August 2016) - Huang, Chunkai; Shi, Yijing; Gamal El-Din, Mohamed; Liu, Yang
Abstract: Effects of hydraulic retention time (HRT) and the chemical oxygen demand/nitrogen (COD/N) ratio on the microbial community composition of integrated fixed-film activated sludge (IFAS) and its ability to treat raw and ozonated oil sands process-affected water (OSPW) were evaluated. After 11 months of HRT and ammonium optimization, 54.56% of the COD and 30.20% of the acid extractable fraction (AEF) were removed in raw OSPW IFAS, and 56.83% of the COD and 51.51% of the AEF were removed in ozonated OSPW IFAS. Extension of the HRT in the IFAS had no significant effect on the removal of COD and nitrogen, whereas a lower COD/N ratio increased the removal of organics and total nitrogen. The quantitative polymerase chain reaction ( q -PCR) indicated that the abundance of nitrifier and denitrifier genes decreased during HRT optimization, and increased significantly after ammonium optimization. Proteobacteria, Nitrospirae, Acidobacteria, and Bacteroidetes were the dominant phyla in IFAS flocs and biofilms according to 454 sequencing. Proteobacteria showed significant decreases in flocs and biofilms after HRT and ammonium IFAS optimization. Nitrospirae and Acidobacteria showed significant upward trends in all biomass forms in optimized IFAS systems compared to unoptimized IFAS systems. Highlights: HRT and COD/N ratio have significant effects on the biodegradation of AEF from OSPW. The abundances of nitrifier and denitrifier genes changed significantly after HRT and ammonium optimization. HRT and COD/N ratio significantly affected the microbial community structure of flocs and biofilms.